STUDY OF INFLUENCE OF FORMULATION AND PROCESS VARIABLES ON ENTRAPMENT EFFICIENCY AND PARTICLE SIZE OF FLOATING MICRO BALLOONS OF DIPYRIDAMOLE BY DOE - KRISHNA, SEELAM RAMYA; RAMU, A.; VIDYADHARA, S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: In the current research work, dipyridamole, a BCS class–II drug, was aimed to be formulated as floating controlled release microballoons using ethyl cellulose as polymer and span 80 as surfactant to improve the gastric retention of drug as the multi-particulate dosage forms have tremendous advantages over single unit dosage forms. Methods: Microballoons were prepared by the emulsion solvent evaporation method. Prepared microballoons were characterized for entrapment efficiency, particle size, floating behavior and drug release studies. The study of effect of various formulation and process parameters like surfactant concentration, solvent volume, the volume of internal phase, polymer concentration, rotation speed on the drug entrapment efficiency and particle size of the microballoons were carried by using Box–Benhken to optimize the formulated microballoons. Results: The smallest particle size of the microballoons was found to be 205.9 µm in the F32 formulation. The highest drug entrapment efficiency was found to be 93.4% in the F34 formulation. Buoyancy studies showed all the formulations have good floating characteristics that lasted for a minimum of 24 h. The maximum yield of microballoons was found in the F7 formulation with 91.8% yield. The final results were statistically treated using ANOVA and were found to be significant (p value<0.05). Conclusion: Thus, the obtained results and their statistical interpretations indicated floating microballoons of dipyridamole were formulated effectively.